Odpowiedzi

2010-03-22T18:08:03+01:00
A)1/2x-4=x-6
1/2x-x=-6+4
-1/2x=-2 /*2
-x=-4
x=4

b)x-5=1/3x+1
x-1/3x=1+5
2/3x=6 /*3
2x=18 /:2
x=9

c)x/4-1/4=2
x/4=2+1
x/4=3 /*4
x=12

d)x/5-3=x=1/5
x/5+x=1/5 +3 /*5
x+5x=1+15
6x=16 /:6
x=16/6 =2i4/6

e)5/6(x-1)=4
5/6x-5/6=4 /*6
5x-5=24
5x=24+5
5x=29 /:5
x=29/5 =5i4/5

f)-1/2(-x-6)=-x
1/2x+3=-x
3=-x-1/2x /*2
6=-2x-x
6=-3x /:3
-x=2
x=-2
2010-03-22T18:28:16+01:00
A)1/2x-4=x-6
1/2x-x=-6+4
-1/2x=-2 *-2
x=4
b)x-5=1/3x+1
x-1/3x=1+5
2/3x=6 *3/2
x=9
c)x/4-1/4=2
x/4=2+1/4
x/4=8/4+1/4
x/4=9/4
4x=36
x=9
d)x/5-3=x=1/5

e)5/6(x-1)=4
5/6x=48/12+10/12
5/6x=58/12 *6/5
x=58/10
x=5,8
f)-1/2(-x-6)=-x
1/2x+3=-x
1/2x+x=-3
15/10x=-3 *10/15
x=-10/5
x=-2